Incidencia en las relaciones interpersonales y la discriminación intercultural dentro de las aulas de los quintos años de educación básica de la escuela “Jorge Icaza Coronel” de la ciudad de Latacunga en el año lectivo 2012-2013 - Beltrán Sánchez, Luis Iván (2013)
This project focuses on the impact researching about intercultural relationships and discrimination in the classroom of fifth-year of basic education “Jorge Icaza Coronel” school in Latacunga, this topic is generated due to the researchers have detected the problem in the School for that reason the proposal is the development of a motivational talks manual. The population, object of study was composed of authorities, teachers and students of the institution. The analysis of the results showed the lack of knowledge and information about importance of personal relationships and the consequences that occur when someone discriminates children. For the work development has been used, methods and techniques for making three chapters, taking a logical sequence that explain clearly the content, to present the motivational talks manual which is intended to provide a valid tool for the learning development. As a result of this investigation, it finds that the motivational talk’s manual is possible, so this material would help to work on motivation to students, improving their attitude against to the problems that exist in this society. Training children, who grow values, respect for people of different cultures and social classes.